Natural regeneration potential and growth of degraded Shorea robusta Gaert n.f. forest in Terai region of Nepal - Malla, R.; Acharya, B. K. (Banko Janakari, 2018)
Sal (Shorea robusta ) has ecological, economical and socio-cultural importance. It is a dominant species in the Terai and Chure region of Nepal. Natural regeneration is the only relevant regeneration method for Sal in Nepal. This study intended to assess natural regeneration potential of Sal in ploughed and unploughed (control) sites. The study was carried out in Chetaradei of Kapilvastu district in an area of 4.79 ha. Two treatments (control and ground work i.e. ploughed) were applied to assess regeneration potential of Sal. The radius of the sample plots was 2 m, which were laid out systematically and the data were recorded from these plots in three consecutive years. Regeneration density was found higher in control site than ploughed site. T-test for regeneration density in three consecutive measurements showed that there was no significant difference between ploughed and unploughed conditions. The species composition was dominated by Sal in both ploughed and unploughed sites. Species diversity (Shannon Weiner) index was found higher in ploughed site than unploughed site in three consecutive measurements. Moreover, T-test showed that mean height of Sal was not significant in both ploughed and unploughed sites except in the first measurement. This study shows that protection from grazing and fire is essential for natural regeneration of Sal. However, ground work helps to increase tree species diversity but it is not necessary in degraded Sal forest. Banko Janakari A Journal of Forestry Information for Nepal Vol. 28, No. 1, 2018, page: 3-10